2019
DOI: 10.3390/nu11071602
|View full text |Cite
|
Sign up to set email alerts
|

Western Diet-Induced Metabolic Alterations Affect Circulating Markers of Liver Function before the Development of Steatosis

Abstract: Since nutrition might have a significant impact on liver function, we analyzed the early effect of Western-type diet on hepatic tissue and lipid and drug metabolism in Wistar–Kyoto rats (n = 8); eight rats fed with a standard diet were used as controls. Histological analysis of liver tissue was performed, and plasma biochemical parameters were measured. Plasma concentration of six bile acids was determined by ultra-liquid chromatography-tandem mass spectrometry UHPLC-MS/MS. Hepatic gene expressions of enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…Liver function was assessed by measuring biochemical markers, i.e., serum concentrations of albumin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total and conjugated bilirubin [34]. The plasma lipid profile was assessed by measuring triglycerides, total cholesterol, and LDL cholesterol [35]. These plasma biochemical parameters were also measured in 5 rats fed with standard diet.…”
Section: Postprandial Blood Glucose Levels Biochemical and Histologimentioning
confidence: 99%
“…Liver function was assessed by measuring biochemical markers, i.e., serum concentrations of albumin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total and conjugated bilirubin [34]. The plasma lipid profile was assessed by measuring triglycerides, total cholesterol, and LDL cholesterol [35]. These plasma biochemical parameters were also measured in 5 rats fed with standard diet.…”
Section: Postprandial Blood Glucose Levels Biochemical and Histologimentioning
confidence: 99%
“…Many experimental evidences suggested that lipotoxicity, proinflammatory mediators, and oxidative stress may have a central role in this process [3], which can occur in the presence or absence of a high amount of dietary fat ingestion [1]. Moreover, the consumption of imbalanced diets (e.g., excessive fat and sugar intake), as well as the alteration of gut microbiome are involved in NAFLD development and progression [4][5][6]. In particular, high fat and high sugar diets, besides promoting the deposition of fat in the liver, could modify microbiome composition and affect gut barrier integrity, facilitating bacterial translocation and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Many NAFLD models were constituted by hypercaloric/western diet. [7][8][9] Gabbia and colleagues 10 found western diet changed hepatic lipid metabolism and the circulation bile acids in rats, which could represent an early marker of NAFLD development. The global prevalence of NAFLD is approximately 25.2% 11 and NAFLD causes huge social and economic burdens.…”
Section: Introductionmentioning
confidence: 99%